(untitled) (American Journal of Pedagogical and Educational Research, 2023)
The article contains comments on the development of physical culture and sports, students’ skills of high physical activity are formed for many years. Physical education also helps to develop moral, strong-willed qualities, providing physical preparation of the younger generation for life and educating the need for health as a vital value.